Charmonium: comparison between potential models - D. A. Ramírez Zaldívar; F. Guzmán; D. Arrebato (Nucleus, 2019)
Heavy quark cc¯ has been studied in the non relativistic framework using a quark-quark potential as a sum of power of the corresponding distance. The form of potential is based on phenomenological facts. The problem was solved numerically using a program written on C++. Mass spectra and the expectation value of the radius have been estimated for different quantum-mechanical states for cc¯ system. The results have been compared with other similar and recent works. The mass spectra obtained is in acceptable agreement with the experimental data for cc¯ .